2020
DOI: 10.1089/scd.2019.0176
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Human Umbilical Cord-Derived Mesenchymal Stromal Cell Administration in Models of Moderate and Severe Intracerebral Hemorrhage

Abstract: Intracerebral hemorrhage (ICH) is as a life-threatening condition that can occur in young adults, often causing long-term disability. Recent preclinical data suggest mesenchymal stromal cell (MSC)-based therapies as promising options to minimize brain damage after ICH. However, therapeutic evidence and mechanistic insights are still limited, particularly when compared with other disorders such as ischemic stroke. Herein, we employed a model of collagenase-induced ICH in young adult rats to investigate the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 66 publications
2
30
0
Order By: Relevance
“…Similar results have been shown in a model of Alzheimer's disease [34,35] with higher brain distribution of MSCs in diseased animals compared to healthy animals. This was also evidenced in another study performed on mice with cerebral tumors [36], rats and beagle dogs with spinal cord injury [37,38], and rats with intracerebral hemorrhage [39]. Moreover, acute distress respiratory syndrome or liver tumors may also affect the distribution of cells after intravenous injection [40,41].…”
Section: Figurementioning
confidence: 75%
“…Similar results have been shown in a model of Alzheimer's disease [34,35] with higher brain distribution of MSCs in diseased animals compared to healthy animals. This was also evidenced in another study performed on mice with cerebral tumors [36], rats and beagle dogs with spinal cord injury [37,38], and rats with intracerebral hemorrhage [39]. Moreover, acute distress respiratory syndrome or liver tumors may also affect the distribution of cells after intravenous injection [40,41].…”
Section: Figurementioning
confidence: 75%
“…For stem cell therapy, the conventional mode of administration is injection of cells into the brain directly or through blood vessels. However, the method of cells being injected into the brain is invasive, and regarding the method of vascular administration, it has been demonstrated that there were only a few cells homing to the brain or had embolization and possible tumorigenesis risk Mello et al, 2020). Thus, a novel way of intranasal route was applied for MSC transplantation therapy in collagenase IV injected mice (Sun et al, 2015).…”
Section: Msc Transplantation In Rodentsmentioning
confidence: 99%
“…therapy was previously reported to reverse the alterations induced by PAH in mice [14]. This treatment was also successful to interfere with other disease models, such as stroke, in which a high amount of cells was required to improve cerebral dysfunction [26]. In the present work, a lower number of cells in combination with a PDE5 inhibitor was administered, which could reduce the risk of complications related to stem cell therapy, such as pulmonary embolism [27].…”
Section: Discussionmentioning
confidence: 74%